Children’s autonomy in medical decision-making - Tai, Michael Cheng-Teh (Array, 2019)
Should children be allowed to express their opinion in regards to medical treatment or experiment? In the past, the practice seemed to assume that children are not matured enough to make decision affecting their well-being, their guardians therefore are given the power to decide for them. In this article the author will argue that this practice should be changed and children should be allowed to get involved. The author quoted findings of Grootens-Wiegers P., Hein I. M., van den Broek J. M. and de Vires M. C. in regards to children’s ability from developmental and neuroscientific aspects that children actually start knowing their like, dislike, good and bad… from a very young age. Though these processes are gradual, the finding tells us that children are not as immature as we used to think. The author thus argues that children’s autonomy must be respected in some way when medical decision is to be made. At least, they must be told what options are available and seek their opinion.